Research on the Main and Auxiliary Traction System of Large-size Mine Electric-wheel Dump Truck - HU Xian; ZHANG Bangfu; MEI Wenqing; ZHOU Zhiyu (Kongzhi Yu Xinxi Jishu)
At present, auxiliary traction control system of most electric-wheel dump trucks in domestic market is driven by diesel engine to drive cooling fan to dissipate heat, the cooling power cannot be changed by frequency conversion, and the fuel consumption of diesel engine will increase under braking conditions. In addition, the traction strategy adopts the field orientation control, which has the problem of slow torque response under fast switching conditions.In this paper, an integrated main and auxiliary converter of high power electric-wheel dump truck is designed and its traction control system is investigated. In the vehicle traction control system, the main traction system adopts high performance direct torque control algorithm to drive two 960 kW induction motors. For the auxiliary traction system, it is controlled by DC/DC front-end with isolation transformer and then DC/AC back-end inverter. The back-end inverter guarantees stable operation of fan and pump loads in full frequency range. At present, the dump truck loaded with this integrated main and auxiliary traction system has been running stably for 3 571 h in Shanxi Pingsu Open-pit Coal Mine, with a cumulative travel distance of 31 632.4 km and a transportation volume of 1 445 276 tons in total, which shows that this traction system can work stably, reliably and efficiently.